ACHIEVING PRODUCTIVITY THROUGH BUDGETARY REFORM : A PROPOSAL FOR NEGARA BRUNEI DARUSSALAM - Razali Mat Zin (Universitas Trisakti, 2013)
The principle budget and productivity reforms of recent decades have shared a common error whereby they have been preoccupied with measurement while ignoring the incentive environment of public organization and their managers. This paper is an attempt to discuss issues pertaining to Negara Brunei Darussalam budgeting process which focus on a pervasive set of disincentives that penalize productivity improvements. The future of both productivity improvement and the country planning depends upon the incentives we create for the public organizations through the budgetary process. Some strategies to remedy the situation in Brunei are recommended.